2021
DOI: 10.1039/d0py01387k
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ε-lysine) and its derivatives via ring-opening polymerization of biorenewable cyclic lysine

Abstract: Poly(ε-lysine) (ε-PL) is an unusual cationic, naturally-occurring biopolymer furnished by microorganisms fermentation process. ε-PL has attracted extensive attention in the areas from food and cosmetic additives to pesticides and medicine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Our laboratory has described the ROP of a 2,5-dimethylpyrrole-protected cyclic lysine monomer to furnish ε-PL. , In this study, we focused on the development of functional mimics of ε-PL by applying renewable lysine as feedstocks. Cyclic lysine (α-amino-ε-caprolactam) was synthesized according to our previous report .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our laboratory has described the ROP of a 2,5-dimethylpyrrole-protected cyclic lysine monomer to furnish ε-PL. , In this study, we focused on the development of functional mimics of ε-PL by applying renewable lysine as feedstocks. Cyclic lysine (α-amino-ε-caprolactam) was synthesized according to our previous report .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous reports have demonstrated that t- BuP 4 -catalyzed ROP of cyclic lysine monomers offered a viable approach for synthesizing ε-PL and its derivatives with high MWs under mild conditions. , After the successful preparation of the DMCL monomer derived from lysine, t- BuP 4 was used for the ROP of DMCL at 140 °C in dimethylacetamide (DMAC). With a 4.0 mol % loading of t -BuP 4 and 1 equivalent of the coinitiator N -benzoyl-α - dimethylamino-ε-caprolactam ( N -BzDMCL) relative to t -BuP 4 , the polymerization proceeded to reach 88% conversation after 3 h (Table , entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalities and tacticities of polymer chains have a significant influence on the physical and mechanical properties of polymeric materials [20–27] . As a synthetic toolbox, both direct polymerization of functionalized monomers and postpolymerization modification have been devoted to introducing diverse functionalities into polymers, enabling the fine‐tuning and improvement of the thermal and mechanical properties of the pristine polymer [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Functionalities and tacticities of polymer chains have a significant influence on the physical and mechanical properties of polymeric materials. [20][21][22][23][24][25][26][27] As a synthetic toolbox, both direct polymerization of functionalized monomers and postpolymerization modification have been devoted to introducing diverse functionalities into polymers, enabling the fine-tuning and improvement of the thermal and mechanical properties of the pristine polymer. [20] Additionally, significant efforts have focused on synthesizing stereoregular polymers towards high-performance materials, [28][29][30][31][32][33] such as ROP of enantiopure monomers to isotactic polymers.…”
Section: Introductionmentioning
confidence: 99%